Essence and Concept of Financial Results of the Enterprise - Ozodbek, Jumakulov (Research Parks Publishing LLC, 2023)
The concept and essence of the financial results of an enterprise are relevant for any enterprise. After all, it is the financial result that reflects the final result of the organization's activities. The article discusses the definition of financial results from the position of leading economists and scientists, analyzes these concepts and generalizes them.